Implementasi Edukasi dan Exercise Fisioterapi pada Komunitas Ibu Hamil dalam Pencegahan Low Back Pain - Daniya Nur Fadhilah; Rakhmad Rosadi; Eleonora Elsa Sucahyo (Jurnal Abdimas Kesehatan (JAK), 2026)
Pregnancy is often accompanied by lower back pain due to hormonal and biomechanical changes, which can reduce the quality of life for pregnant women. However, the lack of knowledge among pregnant women regarding the causes, prevention, and safe exercises remains a major issue in Tasikmadu Village, Malang City. This activity aims to improve the knowledge and skills of pregnant women in preventing lower back pain through education and physical therapy exercises. This activity was held on April 11, 2026, at the Tasikmadu Subdistrict Posyandu in Malang City, with 15 pregnant women participating. The methods applied included an initial screening for back pain using a questionnaire to assess pain intensity (scale 1–10), a pretest to measure participants’ baseline knowledge about the causes and prevention of lower back pain, health education using illustrated posters presented as demonstration and group exercise materials, and a posttest to evaluate knowledge improvement following the intervention. The results of the activity showed that the majority of pregnant women experienced mild to moderate back pain, and there was a significant increase in knowledge following the health education session, as evidenced by the pretest results, which indicated that 73.33% of participants were unaware of the causes of lower back pain and 80% were unaware of how to prevent it. Following the educational session, the post-test results showed a significant improvement, with 100% of participants understanding the causes of lower back pain and knowing how to prevent it. This activity had a positive impact, leading to improved understanding and awareness of the importance of posture and physical activity during pregnancy, as well as the potential for a reduction in lower back pain complaints. Thus, education and exercise are effective as promotive and preventive measures in improving the musculoskeletal health of pregnant women